Bioenergy efficiency of growing indeterminant tomato hybrids in glass winter greenhouses (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The aim of the study was to determine the bioenergetic efficiency of growing indeterminate tomato hybrids in glass winter greenhouses. The experimental research included three main directions: (1) selection of indeterminate tomato hybrids suitable for winter greenhouse conditions; (2) evaluation of the efficiency of scion–rootstock combinations in indeterminate hybrids; and (3) assessment of the influence of plant training methods on the productivity and bioenergetic efficiency of the Merlis F1 hybrid.It was established that when cultivating indeterminate tomato hybrids in glass winter greenhouses, the major components of energy consumption are heating and electricity (63.0%) and labor costs (22.2%). The introduction of the Maximoto F1, Merlis F1, and Torero F1 hybrids increases the energy accumulated in the yield by 15.3–24.7% and raises the bioenergetic efficiency coefficient to 2.01–2.08. The use of scion–rootstock combinations (Merlis F1 and Torero F1 scions grafted onto Maxifort F1, TD-1 F1, and Emperador F1 rootstocks) enhances the energy content of the yield by 11.5–22.6% (3.94–8.38 MJ/m²) and ensures a bioenergetic efficiency coefficient ranging from 2.15 to 2.55.For the Merlis F1 hybrid, training plants into two stems (after the third cluster on every second plant in the slab and after the ninth cluster on every fourth plant) resulted in a significant increase in the energy accumulated in the yield (by 16.9%), providing a bioenergetic efficiency coefficient of 2.28. The proposed technological practices are recommended for implementation in greenhouse vegetable production systems in Ukraine.
Keywords: tomato; glass winter greenhouse; hybrids; variety-rootstock combinations; bioenergy efficiency coefficient